Liquid Biopsy Testing for the Management of Patient with Non-Small Cell Lung Cancer Carrying a Rare Exon-20 EGFR Insertion. (28th January 2022) - Morabito, Alessandro; Manzo, Anna; Montanino, Agnese; Rachiglio, Anna Maria; Sforza, Vincenzo; Pasquale, Raffaella; Costanzo, Raffaele; Maiello, Monica R; Sandomenico, Claudia; Gallo, Marianna; Palumbo, Giuliano; De Luca, Antonella; et al.
Abstract: Increasing evidence suggests that liquid biopsy might play a relevant role in the management of metastatic non-small cell lung cancer (NSCLC) patients. Here, we show how the Molecular Tumor Board (MTB) in our cancer center employed liquid biopsy to support therapeutic decisions in a patient with NSCLC carrying a rare EGFR mutation. A 44-year-old woman, never-smoker with an EGFR, ALK, and ROS1-negative lung adenocarcinoma and multiple brain metastases received systemic therapy and surgery before being referred to our Institute. The MTB suggested NGS testing of tumor biopsy that revealed a rare exon-20 EGFR insertion (p.His773dup; c.2315_2316insCCA) and EGFR amplification. The MTB recommended treatment with erlotinib and follow-up with liquid biopsy, by using both cell-free DNA (cfDNA) and circulating tumor cells (CTCs). An increase of EGFR mutation levels in cfDNA revealed resistance to treatment about 6 months before clinical progression. Extremely low levels of EGFR p.T790M were detected at progression. Based on preclinical data suggesting activity of osimertinib against EGFR exon-20 insertions, the MTB recommended treatment with brain and bone radiotherapy and osimertinib. A dramatic reduction of EGFR mutation levels in the cfDNA was observed after 4 weeks of treatment. The PET scan demonstrated a metabolic partial remission that was maintained for 9 months. This case supports the evidence that liquid biopsy can aid in the management of metastatic NSCLC. It also suggests that treatment with osimertinib might be a therapeutic option in patients with EGFR exon-20 insertions when a clinical trial is not available. Abstract : Increasing evidence suggests that liquid biopsy might play a relevant role in the management of metastatic non-small cell lung cancer (NSCLC) patients. This article reports how the Molecular Tumor Board in one cancer center used liquid biopsy to support therapeutic decisions for a patient with NSCLC carrying a rare EGFR mutation detected by NGS testing of tumor tissue.